Effects of selenium-enriched yeast and astragalus polysaccharide on slaughter performance, serum biochemical and antioxidant indexes of mule duck - LI Li; MIAO Zhongwei; XIN Qingwu; ZHU Zhiming; ZHANG Linli; LI Zhongrong; ZHENG Nenzhu (浙江大学学报. 农业与生命科学版, 2017)
It is important to improve the health level and production performance of poultry through nutritional regulation and control techniques. Adding antioxidants to diets is becoming an economical and effective nutritional regulation method to improve the antioxidant capacity and meat quality of poultry.The objective of this experiment is to study the effects of selenium- enriched yeast, astragalus polysaccharide, and their mixture on the slaughter performance, serum biochemical indexes, and serum antioxidant indexes of mule duck.Two hundred and eighty one-day-old healthy mule ducks were fed under the same condition, and the pre-trial period was 1-21 d. Then 144 mule ducks with similar initial body mass were selected and divided into four groups with three replications per group according to a completely randomized design. The control group was fed with a basal diet, and the experimental groups were fed the basal diet added with 0.3% selenium-enriched yeast (SY group), 300 mg/kg astragalus [Astragalus membranaceus (Ffisch.) Bge.] polysaccharide (APS group), and 0.3% selenium-enriched yeast + 300 mg/kg astragalus polysaccharide (mixture group), respectively. Twelve ducks with similar body mass from each group were randomly selected for slaughter to determine the slaughter performance, serum biochemical indexes and serum antioxidant indexes at the 70th day.The results showed that, except the semi-eviscerated rate of the mixture group was higher than that of the control group (P<0.05), the carcass rate, eviscerated rate, breast muscle rate and leg muscle rate in experimental groups were higher than those of the control group with no significant difference (P>0.05), and the abdominal fat rate and sebum rate were lower than those of the control group with no significant difference (P>0.05). The serum uric acid level of the mixture group was significantly lower than the control group (P<0.01), but significantly higher than the APS group (P<0.05). The serum urea nitrogen content of the mixture group was significantly lower than that of the control group and APS group (P<0.05). The activity of serum lactate dehydrogenase in the experimental groups significantly decreased (P<0.05), and there was no significant difference among the three experimental groups (P>0.05). Compared with the control group, the serum albumin and globulin contents of experimental groups showed an increase trend (P>0.05), while the total protein content, ratio of albumin to globulin, cholesterol content, glutamic oxalacetic transaminase and alkaline phosphatase activity exhibited a decrease trend (P>0.05). The activity of serum glutathione peroxidase (GSH-Px) and total antioxidant capacity (T-AOC) of the mixture group significantly increased compared with the control group (P<0.05), and the serum T-AOC activity of the mixture group was significantly higher than that of the APS group (P<0.05). The serum superoxide dismutase (SOD) activity of the experimental groups increased compared with the control group, but with no significant difference (P>0.05). The content of serum malondialdehyde (MDA) of the mixture group and SY group were significantly lower than the control group (P<0.05).In conclusion, adding selenium-enriched yeast, astragalus polysaccharide, and their mixture to the basal diet of mule ducks have no significant effects on their slaughter performance, but can decrease abdominal fat rate and sebum rate to some extent, reduce the content of serum urea nitrogen and uric acid, and improve the serum immune biochemical indicators and antioxidant capacity of mule ducks.